Intranasal ketorolac and opioid in treatment of acute renal colic - Massimiliano Etteri; Marta Maj; Carlo Maino; Riccardo Valli (Emergency Care Journal, 2018)
The usual treatment of pain in acute renal colic is analgesic in intravenous (IV) route. We tried a rapid, non-painful, non-invasive route of administration using intranasal ketorolac plus fentanyl versus IV standard treatment with non steroidal anti-inflammatory drug plus opioid for the relief of pain in renal colic presenting patients to an Emergency Department (ED). We conducted a prospective nonblinded clinical trial. A sample of 82 adult patients with clinical diagnosis of acute renal colic was included to receive either intravenous ketorolac plus fentanyl or intranasal ketorolac plus fentanyl. Pain score was rated by using a 10 cm visual analogue scale at 0, 30 and 60 minutes after the treatment. Primary outcome was pain reduction. Secondary outcomes were adverse events and rescue treatment. Eighty-two patients were enrolled. The first forty-one patients received intranasal ketorolac plus fentanyl and the second forty-one received intravenous ketorolac plus fentanyl. There were not statistically significant differences in reduction of pain between the two groups at 30 and 60 minutes (P-value at 30=0,225; P-value at 60=0,312) although the trend was in favour of IV group. There were no significant differences between the groups with regard to secondary outcomes (adverse events and rescue treatment). Intranasal ketorolac and fentanyl are equivalent in analgesic effect to intravenous ketorolac and fentanyl treatment for ED patients with acute renal colic and the intranasal treatment can be considered a valid alternative to the standard intravenous treatment.